Asymmetries in bank lending behaviour. Austria during the 1990s - Sylvia Kaufmann (European Central Bank (ECB), 2001)
This paper investigates both cross-sectional asymmetry (related to bank-specific characteristics like size and liquidity) and asymmetries over time (potentially related to the overall state of the economy) in Austrian bank lending reaction to monetary policy. The first type of asymmetry is accounted for by including interaction terms, and the second type is captured by latent state-dependent parameters. Estimation is cast into a Bayesian framework, and the posterior inference is obtained using Markov chain Monte Carlo simulation methods. The results document a significant asymmetric effect of interest rate changes over time on bank lending. During economic recovery, lagged interest rate changes have no significant effect on lending. Where the effects are significant, liquidity emerges as the bank characteristic that determines cross-sectional asymmetry.
Keywords: C11; C23; E51; 330; Asymmetry; bank lending; Markov chain Monte Carlo; Markov switching